The impact of gate-oxide breakdown on common-source-amplifiers with diode-connected active load in low-voltage CMOS processes - Chen, Jung-Sheng; Ker, Ming-Dou (My University, 2007)
The influence of gate-oxide reliability on common-source amplifiers with diode-connected active load is investigated with the nonstacked and stacked structures under analog application in a 130-nm low-voltage CMOS process. The test. conditions of this work include the dc stress, ac stress with dc offset, and large-signal transition stress under different frequencies and signals. After overstresses, the small-signal parameters, such as small-signal gain, unity-gain frequency, phase margin, and output dc voltage levels, are measured to verify the impact of gate-oxide reliability on circuit performances of the common-source amplifiers with diode-connected active load. The small-signal parameters of the common-source amplifier with the nonstacked diode-connected active-load structure are strongly degraded than that with the stacked diode-connected active-load structure due to a gate-oxide breakdown under analog and digital applications. The common-source amplifiers with diode-connected active load are not functionally operational under digital application due to the gate-oxide breakdown. The impact of soft and hard gate-oxide breakdowns on the common-source amplifiers with nonstacked and stacked diode-connected active-load structures has been analyzed and discussed. The hard breakdown has more serious impact on the common-source amplifiers with diode-connected active load.
Keywords: analog integrated circuit; common-source amplifier; dielectric breakdown; gate-oxide reliability; hard breakdown; soft breakdown